Design of a backup voltage supply in a medium-voltage cubicle control panel circuit when a blackout occurs from PLN - Hendra Gillbert; Rahmat Hidayat (Muhammadiyah University, Sidoarjo, 2022)
Uninterruptible Power Supply (UPS) is an important component that is useful for temporarily storing electrical energy. This storage is done in the UPS battery itself, the capacity of each battery is different. Indirectly this UPS is also useful in order to avoid flickering when the electric current from the PLN goes out. This is done in order to avoid damage to the electronic device. In Angkasapura II Bandung as well, UPS is used to avoid flickering which causes damage and even crashes on the plane due to a communication failure between the Pilot and the AFL. Another obstacle is the cubicle control panel circuit. This happens because when there is a blackout from the PLN UPS, the active UPS does not back up this circuit, the bad thing that happens is that the electrical control at Angkasapura will stop because the cubicle control circuit does not receive electricity supply. From the results of this study resulted in a new circuit that can read-up power automatically with the existing UPS.